Heart Disease, Hypertension, Gestational Diabetes Mellitus, and Preeclampsia/Eclampsia in Mothers With Juvenile Arthritis: A Nested Case–Control Study. Issue 2 (February 2017) - Feldman, Debbie E.; Vinet, Évelyne; Bérard, Anick; Duffy, Ciarán; Hazel, Beth; Meshefedjian, Garbis; Sylvestre, Marie‐Pierre; Bernatsky, Sasha
Abstract : Objective: To determine whether women with a history of juvenile arthritis are at higher risk for heart disease and hypertension and for developing adverse maternal outcomes: gestational diabetes mellitus, maternal hypertension, and preeclampsia/eclampsia. Methods: We designed a nested case–control study from a cohort of first‐time mothers with prior physician billing codes suggesting juvenile arthritis, and a matched comparison group without juvenile arthritis. For the nested case–control design, we selected 3 controls for each case for the outcomes of heart disease (n = 403), prepregnancy hypertension (n = 66), gestational diabetes mellitus (n = 285), maternal hypertension (n = 561), and preeclampsia/eclampsia (n = 236). We used conditional logistic regression, adjusting for maternal age and education. Results: Having juvenile arthritis was associated with heart disease (odds ratio [OR] 2.44 [95% confidence interval (95% CI) 1.15–5.15]) but not with gestational hypertension, diabetes mellitus, or preeclampsia/eclampsia. All 66 cases of prepregnancy hypertension had juvenile arthritis. Having prepregnancy hypertension was strongly associated with preeclampsia/eclampsia (OR 8.05 [95% CI 2.69–24.07]). Conclusion: Women with a history of juvenile arthritis had a higher risk of heart disease. This risk signals the potential importance of cardiac prevention strategies in juvenile arthritis. As this was a retrospective study, it was not possible to correct for some relevant potential confounders. Further studies should assess the impact of medications, disease severity, and other factors (e.g., obesity) on cardiac outcomes in juvenile arthritis.